2020
DOI: 10.1370/afm.2492
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Diabetes Care With and Without Certification as a Medical Home

Abstract: PURPOSE The purpose of this study was to assess whether primary care practices certified as medical homes differ in having the practice systems required for that designation and in attaining favorable outcomes for their patients with diabetes, and whether those systems are associated with better diabetes outcomes.METHODS We undertook a cross-sectional observational study, Understanding Infrastructure Transformation Effects on Diabetes (UNITED), of 586 Minnesota adult primary care practices, comparing those tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…We began with quantitative methods to assess primary care performance based on consistently reported practice outcomes for patients with diabetes in relation to variables like medical group size, practice context ( i . e ., urban/rural) [ 12 ], and medical home certification [ 7 , 27 ]. Through this work the study team identified associations between care management processes and quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We began with quantitative methods to assess primary care performance based on consistently reported practice outcomes for patients with diabetes in relation to variables like medical group size, practice context ( i . e ., urban/rural) [ 12 ], and medical home certification [ 7 , 27 ]. Through this work the study team identified associations between care management processes and quality.…”
Section: Discussionmentioning
confidence: 99%
“…Given the UNITED study’s focus on identifying specific changeable factors and strategies that are most effective in producing high-quality outcome scores, selection was limited to practices that performed in the top quartile statewide on the composite of the five diabetes quality measures for the most recent year with available data (2018). Selection further included only those practices that returned the Physician Practice Connections–Research Survey in both 2017 and 2019; collected as part of the UNITED study’s mixed-method approach, this survey was used to assess a practice’s systematic use of care management processes [ 7 , 8 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Quantitative analyses of this data set have been published. 7,8 Quantitative Data Study participation depended on having a clinic leader complete a 112-question survey in 2017 regarding the presence of various care management processes to support high-quality care for patients with chronic medical conditions. The survey was created and tested for reliability by the National Committee for Quality Assurance and has been widely used.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6][7] Primary care physicians (PCP) care for over 90% of individuals with type 2 diabetes, and recent findings indicate that PCP centric structures that align with the medical home model appear well suited for improving care and outcomes for this patient population. [8][9][10] While these findings are still primarily based on observational studies, related work assessing the effect of Accountable Care Organizations on patient care has indicated evidence of a potential causal link between organizational structure and patient outcomes. 11 With that noted, not all patients receive care in PCP centric structures, and many are instead confronted with fragmented care delivery, which has been shown to reduce quality of care, increase utilization, increase cost, and lead to poorer outcomes.…”
Section: Introductionmentioning
confidence: 99%